Influence of Soybean Oil or Non-Soybean Oil Based Lipid Emulsions on Parenteral Nutrition Associated Liver Disease in Late Preterm and Term Infants - Wong, Rachel S.H.; Walker, Karen; Halliday, Robert; Trivedi, Amit (International Journal of Child Health and Nutrition, 2014)
Background: Total parenteral nutrition (TPN) is a life-saving therapy given to neonates with intestinal failure. However, infants on long-term TPN may experience Parenteral Nutrition-Associated Liver Disease (PNALD). New formulations for lipid emulsions are purportedly better than the traditional soy-based lipid emulsions (SLE). Our primary objective was to determine the prevalence of PNALD in infants who received non-soybean-based lipid emulsions (NSLE) or SLE. Methods: In this retrospective study, medical records of all infants admitted to a tertiary neonatal intensive care unitfrom 2004 to 2013 were reviewed. Late preterm (34 -36 weeks of gestation) and term infants who were on TPN for more than two weeks were included. Their demographic data and clinical variables were collected. Results: 208 infants received SLE for more than two weeks. The prevalence rate of PNALD in those who received SLE was 21% while that of those who received the NSLE was 17%. No significant difference was found between the ‘Soy’ or ‘NonSoy’ subgroups (p = 0.315). Seventy infants received TPN for more than four weeks. The prevalence rate of PNALD in infants who received SLE and NSLE was 35% and 25% respectively. No significant statistical difference was found between the ‘Soy’ or ‘NonSoy’ subgroups (p = 0.132). Conclusions: The type of lipid emulsion does not significantly influence the rate of PNALD in late preterm and term infants on long-term TPN.